The Effect Of 3-Month Contraceptive Injections on Decreased Libido in Women of Childbearing Age at The Pomalaa Health Center - Mien, Mien; Rosmilah, Rosmilah (PT. Nursing Genius Care, 2024)
Background: DMPA injectable contraceptives with high levels of progesterone make the vagina dry so it feels painful during intercourse which can further decrease libido Purpose: . The purpose of this study was to determine the effect of the 3-month injection of family planning on decreasing the libido of women of childbearing age at the Pomalaa Health Center. Methods: This type of quantitative research used a cross sectional study conducted at the Pomalaa Health Center in July involving a sample of 76 people. sampling through purposive sampling technique. Statistical tests were carried out through the chi square test. Results: The results of this study were based on the use of contraceptives, there were 36 people (47.4%) who used 3 months of injection contraception and there were 40 women (52.6%) who did not use 3 months of injection contraception, for the decreased libido variable, there were 42 people ( 55.3%) mild and moderate as many as 34 people (44.7%) and there is an effect of 3 months injection contraception on decreased libido WUS at Pomalaa Health Center with a value of ρ = 0.000 (α < 0.05). Conclusion: There is an effect of 3-month contraceptive injections on decreasing libido in women at the Pomalaa Health Center.